The development of a sense of identity during the adolescent period - Short, Ann Margaret (Department of Psychology, 2016)
This study was motivated by an interest in young people which stemmed from working with ordinary high school pupils and not from the academic study of adolescent psychology. In order to find a suitable subject for research I turned to those books which were likely to give a cross-section of the literature in the field, for example, the survey provided by Gottlieb & Reeves (1963) and various books of 'readings' (Seidman, 1953; Bier, 1963; Mussen,,Conger & Kagan, 1965; Grinder, 1969; Gold & Douvan, 1969). This created an impression of a large number of narrow, insulated empirical studies pragmatically ordered according to various dominant 'themes' (e.g., physical and cognitive development, family and peer relations, values, problems, interests) and relatively few isolated 'theoretical' articles. Few of the empirical studies were grounded in theory or attempted to relate their findings to any theoretical framework, while most of the theoretical articles seemed, to be speculative. The empirical research concerning the development of a self-concept during adolescence aroused my interest but much of it also lacked a theoretical framework. It was then suggested that Erik Erikson's theory of identity formation in adolescence might provide a more comprehensive and coherent framework for an empirical investigation.